2005
DOI: 10.1210/jc.2004-0444
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive Pregnanolone Isomers during Pregnancy

Abstract: The pregnanolone isomers (PI) allopregnanolone (3alpha-hydroxy-5alpha-pregnan-20-one), pregnanolone (3alpha-hydroxy-5beta-pregnan-20-one), isopregnanolone (3beta-hydroxy-5alpha-pregnan-20-one), epipregnanolone (3beta-hydroxy-5beta-pregnan-20-one), progesterone, and estradiol were measured in 138 pregnant women. The sampling was carried out from the first through the 10th month of pregnancy. Gas chromatography-mass spectrometry analysis and RIA were used for the measurement of steroid levels. The ratios of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 56 publications
6
40
1
Order By: Relevance
“…This allopregnanolone level is similar to that during early pregnancy. 36,37 However, progesterone had no significant effect on the mood 24 or state anxiety 25 questionnaires (all P > 0.2) and did not significantly modulate response accuracy or reaction times in the behavioral task (all P > 0.05). These factors therefore appear to have little explanatory value in relation to the observed differences in brain activity between the progesterone and placebo conditions.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This allopregnanolone level is similar to that during early pregnancy. 36,37 However, progesterone had no significant effect on the mood 24 or state anxiety 25 questionnaires (all P > 0.2) and did not significantly modulate response accuracy or reaction times in the behavioral task (all P > 0.05). These factors therefore appear to have little explanatory value in relation to the observed differences in brain activity between the progesterone and placebo conditions.…”
Section: Resultsmentioning
confidence: 83%
“…52 In the present study, an increased responsiveness of the amygdala was observed after increasing the progesterone and the allopregnanolone concentrations from the follicular phase to levels that are naturally occurring during the luteal phase and early pregnancy, respectively. 36,37 The increased amygdala response might therefore be specific for this concentration change, while higher supraphysiological concentrations might eventually decrease amygdala activity, 15 in parallel with increased sedation in humans. 53 These results therefore show that changes in progesterone level that are within the physiological range can increase amygdala activity.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women, the levels of 5Ǐ/ǐ-PM including the GABAergic 3Ǐ-PI are persistently elevated (M. Hill, et al, 2007;M. Hill, Parizek, Kancheva, et al, 2010;Kancheva, et al, 2007;Luisi, et al, 2000;Mickan & Zander, 1979;Parizek, et al, 2005;Pearson Murphy, Steinberg, Hu, & Allison, 2001). Their concentrations in women after luteo-placental shift reach values about two orders of magnitude higher than the concentrations detected in the FP (Parizek, et al, 2005).…”
Section: Reversible C-3 C-17 and C-20 Oxidoreductive Inter-conversiomentioning
confidence: 99%
“…Hill, Parizek, Kancheva, et al, 2010;Kancheva, et al, 2007;Luisi, et al, 2000;Mickan & Zander, 1979;Parizek, et al, 2005;Pearson Murphy, Steinberg, Hu, & Allison, 2001). Their concentrations in women after luteo-placental shift reach values about two orders of magnitude higher than the concentrations detected in the FP (Parizek, et al, 2005). Pearson Murphy et al show that the levels of C21 steroids including 5α/β-PM rise greatly during pregnancy, being the highest for progesterone (562-fold the FP level), 5Ǐ-DHP (161-fold), 3ǐ,5Ǐ-THP (56-fold), 3Ǐ,5Ǐ-THP (37-fold), pregnenolone (30-fold), 5ǐ-DHP (16-fold) and 3ǐ,5ǐ-THP (16-fold) at 37 th week of gestation (Pearson Murphy, et al, 2001).…”
Section: Reversible C-3 C-17 and C-20 Oxidoreductive Inter-conversiomentioning
confidence: 99%
See 1 more Smart Citation